1999
DOI: 10.1038/7036
|View full text |Cite
|
Sign up to set email alerts
|

Improving plant drought, salt, and freezing tolerance by gene transfer of a single stress-inducible transcription factor

Abstract: Plant productivity is greatly affected by environmental stresses such as drought, salt loading, and freezing. We reported previously that a cis-acting promoter element, the dehydration response element (DRE), plays an important role in regulating gene expression in response to these stresses. The transcription factor DREB1A specifically interacts with the DRE and induces expression of stress tolerance genes. We show here that overexpression of the cDNA encoding DREB1A in transgenic plants activated the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

48
1,317
8
17

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,843 publications
(1,406 citation statements)
references
References 33 publications
48
1,317
8
17
Order By: Relevance
“…Among the DRE binding proteins, the DREB2 subfamily has been reported to be induced by drought and high salinity stress. Transgenic Arabidopsis plants expressing DREB1 B/ CBF1 or DREB1 A/CBF3 under the control of CaMV 35S promoter showed strong tolerance to freezing, drought and high salinity stresses suggesting that DREBs/CBFs target multiple genes (Jaglo-Ottosen et al 1998;Liu et al 1998;Kasuga et al 1999). Microarray analyses have indicated that these factors target stress inducible genes containing the conserved DRE or DRE-related core motifs in their promoter regions (Maruyama et al 2004).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the DRE binding proteins, the DREB2 subfamily has been reported to be induced by drought and high salinity stress. Transgenic Arabidopsis plants expressing DREB1 B/ CBF1 or DREB1 A/CBF3 under the control of CaMV 35S promoter showed strong tolerance to freezing, drought and high salinity stresses suggesting that DREBs/CBFs target multiple genes (Jaglo-Ottosen et al 1998;Liu et al 1998;Kasuga et al 1999). Microarray analyses have indicated that these factors target stress inducible genes containing the conserved DRE or DRE-related core motifs in their promoter regions (Maruyama et al 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Drought tolerance is a complex trait that is being influenced by multiple genes, interactions among genes and environmental cues (Tardieu and Tuberosa 2010). Perception of stress signals and activation of complex signaling pathways bring about drastic changes in the cellular gene expression which is a prerequisite for plants to acclimatize under extreme conditions (Kasuga et al 1999;Tong et al 2007). It is well established that almost all biotic and abiotic stresses induce oxidative stress by producing higher levels of reactive oxygen species (ROS) such as hydrogen peroxide (H 2 O 2 ), superoxide anion (O 2…”
Section: Introductionmentioning
confidence: 99%
“…Another important aspect involves the regulated and targeted expression of transgenes, such as by use of stress regulated promoters e.g., rd29 (Kasuga et al, 1999), 6XARE (Rahman et al, 2001), 4ABRC-Act1-100P-Hva22 (Garg et al, 2002;Roy and Wu, 2002;Rohila et al, 2002), AIPC (ABA-induced promoter complex, Zhu et al, 1998), Gmhsp17.6-L (Lee andSchoffl, 1996). AIPC (ABA induced promoter complex) has also been used in conferring salt and water stress tolerance by engineering P5CS in rice .…”
Section: Prospects For Genetic Engineeringmentioning
confidence: 99%
“…Just 1 year ago, European Commission, who once kept conservative to biotechnological breeding, constructed a big project: Plants for the Future: a European vision for Plant Biotechnology towards 2025, in which much is involved in resistance drought [14]. Many advances in relation to this hot topic, including molecular mechanism of anti-drought and corresponding molecular breeding have taken place [28,33,34,39,44,47,50,53,[55][56]63,[72][73][74][75]78]. Although the obtained transgenic crops (mainly, wheat) by different types of gene technology all exhibit drought resistance to some extent, they have many shortfalls related to agronomical performance and/or development [47,49,53,62,66,68,74].…”
Section: Introductionmentioning
confidence: 99%